The Role of Thermomechanical and Aeroelastic Optimization in FRP-Strengthened Structural Elements for High-Performance Aerospace and Civil Applications - Selasi Agbale Aikins; Francis Asare Baffour Yeboah; Lawrence Anebi Enyejo (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
Fiber Reinforced Polymers (FRP) have revolutionized the field of structural engineering, particularly in aerospace and civil applications, by providing lightweight, high-strength, and corrosion-resistant solutions for structural enhancement. However, the structural efficiency of FRP-strengthened elements is often governed by thermomechanical and aeroelastic behavior, necessitating advanced optimization techniques to ensure performance under extreme loading conditions. This review explores the role of thermomechanical and aeroelastic optimization in improving the structural resilience and longevity of FRP-reinforced components in high-performance applications. The paper systematically examines the key parameters influencing FRP-enhanced structural members, including temperature-dependent mechanical degradation, interfacial debonding, and stress redistribution under fluctuating thermal and aerodynamic loads. Advanced computational models and experimental validation methods for optimizing FRP-strengthened structures are critically analyzed. Furthermore, the paper highlights emerging strategies such as multi-scale modeling, topology optimization, and adaptive hybrid reinforcement techniques to mitigate failure risks associated with thermal expansion mismatches, flutter instabilities, and fatigue-induced delamination. Case studies in aerospace and civil infrastructure applications are discussed to showcase the effectiveness of thermomechanical and aeroelastic optimization in enhancing load-bearing capacities, minimizing vibration-induced damage, and improving the energy absorption characteristics of FRP-reinforced structures. This review synthesizes state-of-the-art methodologies, identifies existing challenges, and outlines future research directions for optimizing FRP-strengthened structural elements, providing a comprehensive reference for engineers and researchers striving to advance the integration of FRP composites in next-generation aerospace and civil engineering applications.
Keywords: Fiber Reinforced Polymers; Thermomechanical Optimization; Aeroelastic Stability; Structural Reinforcement; High-Performance Aerospace; Civil Engineering Applications